Synthetic lighweight coarse aggregate (SYLCAG) concrete using artificial offshore sand - Muhammad Nazrin Akmal, Ahmad Zawawi (2014)
Concrete is a rough building material that are made from a mixture of aggregate, sand, cement and water, that can be spread or poured into molds and that forms a mass on hardening. Aggregate is a granular mineral material such as sand, gravel, crushed stone that be used with a bonding medium It will undergo substantial wear and tear throughout life. In general, it should be hard and tough enough to resist crushing, degradation and disintegration from any activities. Currently, there are increasing demand on coarse aggregate. So, one alternative are taken which is produce artificial coarse aggregate and some of them is lightweight. This research, is about the production of artificial lightweight coarse aggregate (SYLCAG) by using artificial offshore sand with 1300 kg/rn 3 of density which is 54% lighter than normal aggregate. That SYLCAG was be used in concrete to replace fully function of normal aggregate and also make the concrete more lightly. The SYLCAG will be tested by LA abrasion test and crushing value test. Then, that SYLCAG is used to produce SYLCAG concrete with 75% density compared to normal concrete density and will be test by compressive strength test and flexural test to get it properties. As conclusion, this aggregate produced have a potential to further use in construction industry for part that have experience less forces like wall or partition.